Data Analysis-Driven Precise Asthmatic Treatment by Targeting Mast Cells - Tan, Yupin; Zou, Lili; Li, Na; Huang, Li; Chen, Meiji; Li, Xuexiang; Zheng, Xue; Li, Wenkai; Li, Yun; Yang, Chun-Tao (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2021)
Background: Although the importance of mast cells in asthma has been studied, mast cellsinduced global changes in lungs are largely unknown. Data-driven identification contributes to discovering significant biomarkers or therapeutic targets, which are the basis of effective clinical medications. Objective: This study aims to explore the effects of mast cells on gene expression in asthmatic lungs, and to assess the curative effects of inhaled budesonide (BUD). Methods: Pulmonary gene expression in KitWsh mice with or without mast cell engraftment was analyzed with R software. Functional enrichment of Gene Ontology and KEGG was carried out through the DAVID online tool. Hub genes were identified with String and Cytoscape software. Results: The array analyses showed that the mast cell engraftment enhanced inflammation/immune response, cytokine/chemokine signal, and monocyte/neutrophil/lymphocyte chemotaxis. Interleukin (IL)-6 was identified to be a significant hub gene with the highest interaction degree. Based on this, the effects of BUD were investigated on the aspects of anti-inflammation. BUD’s treatment was found to reduce serum IL-6 content and pulmonary inflammation in ovalbumin-induced asthma rats. The treatment also downregulated beta-tryptase expression both in lung tissues and serum. Morphologically, the accumulation and degranulation of mast cells were significantly suppressed. Notably, the effects of BUD on inflammation and degranulation were comparable with Tranilast (a classic mast cell inhibitor), while a remarkable synergy was not observed. Conclusion: This study presented a unique pulmonary gene profile induced by mast cell engraftment, which could be reversed through blockage of mast cells or inhaled BUD.
Keywords: Asthma